PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN PEREKONOMIAN MELALUI OBYEK WISATA WADUK MALAHAYU - Nurhayati Nurhayati (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2019)
The needs and potential of the community are the main considerations in empowerment activities. Some natural, social and cultural resources of the region also have the potential to be developed into tourist destinations. The development of the potential of this tourist area can be a potential resource for generating income, creating jobs, and can condition the attitudes and behaviors of a dynamic community to develop. In its development and development, of course it cannot be separated from the participation of the surrounding community. This reseacrh aims to explain: To find out community participation in the development and construction of Waduk Malahayu. And To find out the impact of community economic development through Waduk Malahayu. This reseach uses qualitative methods where the research procedure produces descriptive data in the form of written words from the people observed. As for data collection using observation, interviews and documentation. Based on research conducted that community participation in the development of the Waduk Malahayu is participation in the form of delivering ideas, participation in the form of energy, participation in the form of expertise and participation in the form of property. Furthermore, there are several impacts felt by the community with the development of Waduk Malahayu, namely, increased community skills, increased community walfare, availability of jobs, infrastructure development, and availability of entertainment.